CALCULATION OF PAVEMENT PERMANENT DEFORMATION USING PERZYNA’S ELASTO-VISCOPLASTIC MODEL - Tai, Nguyen Huynh Tan (Vietnam Journal of Science and Technology, 2016)
In this work, a method for calculation of pavement permanent deformation due to traffic loading is presented. The mechanics behavior of asphalt concrete layer is considered as Perzyna’s elasto-viscoplastic material. The pavement permanent deformation is incrementally calculated using nonlinear finite element method. Model parameters are determined using Hamburg Wheel Tracking Test result.